2017
DOI: 10.1136/bmjopen-2017-018632
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of preoperative medical consultations by internal medicine physicians: a systematic review

Abstract: ObjectiveClinics have been established to provide preoperative medical consultations, and enable the anaesthetist and surgeon to deliver the best surgical outcome for patients. However, there is uncertainty regarding the effect of such clinics on surgical, in-hospital and long-term outcomes. A systematic review of the literature was conducted to determine the effectiveness of preoperative medical consultations by internal medicine physicians for patients listed for elective surgery.DesignSystematic searches of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…32,40,41 This suggests a role well beyond clinical consultation and may explain why these complex interventions appear to show more promise than preoperative physician consultation as a single strategy. 11 However, this complexity also leads to potential variability within and between services and reliance on good communication and teamwork. 41 Evaluation designs, such as cluster randomization or well-conducted interrupted time series designs, would be appropriate for these complex interventions 42 well as variable descriptors of physician-led interventions, there is a possibility that we missed important studies in our search.…”
Section: Discussionmentioning
confidence: 99%
“…32,40,41 This suggests a role well beyond clinical consultation and may explain why these complex interventions appear to show more promise than preoperative physician consultation as a single strategy. 11 However, this complexity also leads to potential variability within and between services and reliance on good communication and teamwork. 41 Evaluation designs, such as cluster randomization or well-conducted interrupted time series designs, would be appropriate for these complex interventions 42 well as variable descriptors of physician-led interventions, there is a possibility that we missed important studies in our search.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon and clinic physician relationship has also not been well described in previous studies,4 making it difficult to determine whether the clinic physician provided a stand-alone consultation with no postoperative patient follow-up or an integrated approach to patient care between the surgeon and clinic physician. The clinic physician in this study was considered a member of surgical teams with expertise on the medical management of patients in preparation for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A set of potentially modifiable comorbidities have been identified to be associated with increased length of hospital stay and postoperative complications 3. Patients with poorly controlled modifiable comorbidities can be referred for medical optimisation prior to elective surgery at the discretion of the surgical consultant, but the factors that influence this referral are not well understood 4. Further, there has been minimal detail published on the actual services provided as part of the medical optimisation of patients and its design and implementation has been heterogeneous to date 4…”
Section: Introductionmentioning
confidence: 99%
“… 10 Other studies have reported an increased length of stay, costs and post-operative complications in patients who had a PAME. 11 This data may be biased if patients who were referred for a PAME were higher risk or had poorer functional capacity. Regardless, PAMEs continue to be an essential part of surgical care, often due to practice tradition, medico-legal concerns, and to avoid any potential delays.…”
Section: Introductionmentioning
confidence: 99%